Rowing biomechanics & psychology - Kleshnev, V. (Rowing Biomechanics Newsletter, 2014)
The authors here try to summarise psychological effects of biomechanical measurement and evaluation procedure. As we hadn`t used psychological research methods, these are only subjective observations, though they were quite consistent. Biomechanics could assist psychology in three main areas: to increase motivation, decrease anxiety and improve collaboration in teams.